Biomarkers of balance and gait deficits in FMR1 premutation carriers: a mini-review - Moore, Leila C.; Maltman, Nell; Lee-Confer, Jonathan S.; Kobel, Megan J. (Frontiers in Aging Neuroscience, 2025)
Fragile X-associated tremor/ataxia syndrome (FXTAS) is a neurodegenerative disorder caused by a premutation (PM) of the FMR1 gene on the X chromosome. FXTAS is characterized by intention tremor, ataxia, and cognitive decline. Age-related cognitive-behavioral and sensorimotor (i.e., balance and gait) abnormalities are also present in PM carriers who do not develop FXTAS. Digital biomarkers of gait and balance have been proposed to be promising markers in characterizing prodromal changes in FXTAS (i.e., preFXTAS) and identifying age-related changes in the FMR1 phenotype in those who do not develop FXTAS. In this mini-review, gait and balance findings in PM carriers are reviewed to highlight potential future applications. Variability measures of gait and postural sway reveal measurable impairments in individuals with FXTAS, particularly under conditions challenging sensory integration or assessing cognitive-motor interactions. However, there are limited studies quantifying these domains in FMR1 PM carriers without FXTAS, and there is significant variability in the patient populations assessed (i.e., differing ages, relative lack of information in females) thus restricting conclusions about the progression of balance and gait in FXTAS and possible prodromal markers. Future research should prioritize longitudinal tracking of gait and balance in PM carriers, along with potential cognitive interactions and the characterization of sensory contributions to postural control. This mini-review aims to synthesize current findings on digital balance and gait biomarkers in FMR1 premutation carriers and to explore their potential utility for early FXTAS detection.